Pengembangan LKPD IPA Digital Berpendekatan Konstruktivistik dalam Meningkatkan Kemampuan Literasi Sains Siswa SMP - Bima Brilliando Agam (Borneo Journal of Islamic Education, 2026)
This study aimed to develop a digital Science LKPD based on constructivist learning theory to enhance the scientific literacy skills of junior high school students and to evaluate its effectiveness. This research employed the Research and Development (R&D) method using the 4-D development model. The feasibility and practicality of the media were validated by instructional media experts and science education experts using a Likert scale assessment questionnaire. The media's effectiveness was tested on one class group at SMPN 1 Banyuwangi using a quasi-experimental One-Group Pretest-Posttest design. Data analysis techniques included a Paired T-Test to examine the significance of the improvement between the pretest and posttest results, and the N-gain score method to determine the category of improvement. This study produced a feasible and practical digital Science LKPD characterized by activities that encourage users to actively construct their own understanding through problems presented as digital content. Furthermore, the product proved effective in improving students' scientific literacy skills, as indicated by an increase in posttest scores following the intervention, with a significance level of  and a t-value of -8.216. The improvement between the pretest and posttest scores was demonstrated by an N-gain score of 0.31 (moderate improvement category).